(untitled) (Development Engineering Conferences Center Articles Database, 2024)
Food industry has been criticized for use of non-biodegradable, non-eco-friendly, and toxic production methods, materials and treatment strategies.The environmental impact of persistent plastic wastes is raising general global concern, and disposal methods are limited. The continuously growing public concern in the problem has stimulated research interest in biodegradable natural polymers. Biopolymers (polysaccharides) have various applications in medicine, food and petroleum industries. Microorganisms can produce and excrete good amount of polysaccharides in simple but costly production conditions. A number of polysaccharides produced by microorganisms have either been adopted as commercial products or have the potential for commercialization. The advent of modern biotechnology has fundamentally transformed the way scientists view organisms and the materials they produce. The main drawback limiting the development of these polysaccharides is the lack of efficient processes for their extraction and purification. However new applications in agronomy, foods, cosmetic and therapeutic could in a near future accentuate the effort of research for their development.